ANALISIS PENGARUH PERMINTAAN E-MONEY, JUMLAH UANG BEREDAR (M1), PRODUK DOMESTIK BRUTO (PDB) TERHADAP VELOCITY OF MONEY (VELOSITAS) DI INDONESIA (PERIODE APRIL 2007 – DESEMBER 2017) - RYSQI PUSPITA SARI (PPJP Universitas Lambung Mangkurat, 2019)
This journal investigates, analyzes and understands the influence of the independent variables (e-money demand, M1, GDP) on dependent variable (velocity) in Indonesia from April 2007 to December 2017. It also detects which independent variables have the most influence on performance velocity. The analytical tool use is multiple linear regression, t test, and F test. This study takes data from April 2007 to December 2017. The result of prove that e-money demand is not too partialeffect on velocity, but simultaneously still influential. While M1 and GDP are dominant and have a partial and simultaneous influence on velocity.Keyword: E-Money Demand; Total Money Supply (M1); Gross Domestic Product (GDP); Velocity of Money